Analisis Hukum Ekonomi Syariah dalam Transaksi Akad Qardh PayLater pada Aplikasi Shopee - Muhammad Rivaldy; Rasta Kurniawati Br. Pinem (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The Qardh contract law in muamalat law does not allow the lender to take profit or interest, and this carries usury which is prohibited by Islamic law. This feature uses loans and instant loans with a certain limit amount that can be used for shopping and paid in the following month according to the due date agreed by active users of the marketplace. This research aims to determine the Qardh contract transaction mechanism on Shopee PayLater in accordance with sharia economic law, legal uniformity in prohibiting PayLater, the Shopee Paylater transaction mechanism for online buying and selling using Qardh contracts, and the Shopee Paylater payment system in installments without a credit card. In this research, the type and approach used is empirical, which is usually called field research with a qualitative approach method. Meanwhile, the data collection techniques that researchers use are interviews, observations, documentation and literature review. Then the data analysis used in this research is descriptive qualitative. Based on the results of research and data analysis, it was concluded that the Shopee PayLater transaction mechanism, namely the rules regarding online buying and selling transactions, still refers to the legal terms of the agreement in Article 1320 of the Civil Code. The conditions for a valid agreement in Article 1320 of the Civil Code are as follows: 1) There is an agreement between both parties; 2) The ability to act; 3) The existence of the agreed object; 4) There is a lawful cause. If there is a delay in making payment, the buyer will be subject to a fine of 5%. This amount will continue to increase if the buyer does not immediately pay off the installments. Getting a bad view from the Financial Services Authority (OJK) makes it difficult to get financing from banks or others. Sharia Economic Law regarding Shopee PayLater is whether or not the elements of harmony and buying and selling conditions are met. In practice, regarding the existence of harmony and conditions for buying and selling using Shopee Paylater, it can be explained as follows: 1) Seller and buyer or people who have an agreement (aqid); 2) Sighat (consent and acceptance); 3) Ma'qud'alaih (goods purchased). So, transactions using Shopee PayLater are considered to contain usury.